FOREST COVER CHANGE OF LOWLAND RAINFOREST ECOSYSTEM OF OKOMU NATIONAL PARK, NIGERIA - ADENIJI, A. E.; ADEKUGBE, O. A.; UKOHA, P. A.; OKONKWO, S. J.; ADEWOYE, A. R. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
Okomu National Park is an ecological data bank of tropical flora and fauna species. Some of the flora and fauna are threatened or endemic to the tropical lowland rainforest of Okomu National Park.  This study used Satellite Remote Sensing to quantify the nature and rate of forest changes in Okomu National Park. Multi-temporal 30m resolution Landsat satellite images spanning 20 years (2000, 2010, and 2020) of the study area were acquired. The images were subjected to maximum likelihood supervised classification. The results revealed that the forest cover change of Okomu National Park has reduced drastically, the forest cover which was 88.93% in 2000, reduced to 79.01% in 2010 and 67.37% in 2020. The non-Forest cover increases from 11.07% in 2000 to 20.99% in 2010 and 32.63% in 2020. The findings of the study indicate that the designation of forest-protected status for Okomu National Park did not effectively prevent deforestation during the 20 years under investigation.  The fact that the deforested area expanded during these periods suggests that the existing measures and policies in place were ineffective in preventing or curbing deforestation activities within the national park. It emphasizes the urgent need for stronger and more effective conservation strategies to protect the park's forested areas. To address this issue, the Federal government must reassess and revise the existing policies and management practices related to the national park. This may involve identifying the specific drivers and causes of deforestation and implementing targeted interventions to mitigate them. Additionally, there should be a focus on improving enforcement and monitoring mechanisms to ensure the compliance of individuals and entities operating within the park.